2012
DOI: 10.1142/s0218810412500268
|View full text |Cite
|
Sign up to set email alerts
|

Scaphoid Non-Unions, Where Do They Come From? The Epidemiology and Initial Presentation of 270 Scaphoid Non-Unions

Abstract: Scaphoid injury and subsequent non-union is a well documented and researched subject. This article gives an overview of the epidemiology and results of the patients we have treated for scaphoid non-union at a University Hospital. 283 scaphoid non-unions in 268 patients (83% men) were operated upon, 230 as a primary and 47 as a secondary. The median age at time of surgery was 27 years. One-third of the non-unions were located in the proximal part of the scaphoid and the remaining two-thirds in the middle part. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
2
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 13 publications
0
22
2
8
Order By: Relevance
“…Of particular interest is fracture of the carpal scaphoid 15 23 24. When a scaphoid fracture is suspected clinically but radiographs are negative, CT or MR is often utilised to definitively diagnose the presence of a fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is fracture of the carpal scaphoid 15 23 24. When a scaphoid fracture is suspected clinically but radiographs are negative, CT or MR is often utilised to definitively diagnose the presence of a fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Da der proximale Pol keine eigene, suffiziente Blutversorgung auf-weist, treten nach unbehandelten Skaphoidfrakturen im proximalen Drittel 3-bis 6-mal häufiger Pseudarthrosen und ggf. auch avaskuläre Nekrosen auf [23,28,32].…”
Section: Skaphoidfrakturenunclassified
“…1,2) For clinical purpose it is important to distinguish between non-displaced, displaced and proximal scaphoid fractures because the latter two types are at risk for nonunion. [3][4][5][6] Amirfeyz et al showed that all fractures with signs of consolidation on the CT-scan 4 weeks following trauma will heal with conservative treatment. However, only half of the fractures with >3 mm displacement will heal.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of osteoarthritis increases with time from injury to surgery. 5,9) If there is already evidence of osteoarthritis on preoperative imaging, scaphoid surgery is not advised and other therapy is indicated instead.…”
Section: Introductionmentioning
confidence: 99%